Site Classification System and Site Coefficients for Shallow Bedrock Sites in Korea. Issue 7 (9th August 2018) - Manandhar, Satish; Cho, Hyung-Ik; Kim, Dong-Soo
ABSTRACT: Recent studies have shown that the site coefficients obtained from site response analyses of Korean soil sites are significantly different from those specified in the current Korean seismic code, especially in the short-period portion of site response. This difference is mainly attributed to the shallow bedrock conditions (bedrock depth usually less than 30 m) in Korea. This study proposes a new site classification system and site coefficients for shallow bedrock sites based on site response analyses of more than 300 sites. The proposed site classification scheme and site coefficients proposed in this study are an improvement over the current seismic code and previous studies.